The Evolution of the Chemical Composition of Phosphates as an Evidence of the Multi-Phase Formation of the Alkaline-Carbonate Fluid-Explosive System of the Middle Timan - I. I. Golubeva; V. N. Filippov; A. S. Shuyskiy; I. N. Burtsev (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2023)
he alkaline-carbonate fluid-explosive structure in the Middle Timan includes carbonatites, carbonatized fluidexplosive dikes, and fenitized terrigenous-carbonate rocks of the Riphean. Phosphates, represented by monazite and apatite, are formed in all rocks. The chemical composition of the minerals testifies to the multiphase formation of this structure and a single source of fluids involved in its formation.